Data in the Internet of things age: an overview of data property in commercial, academic and legal perspectives - Sidi Ahmed, Sidi Mohamed; Mohamed, Duryana (2018)
Data is at the heart of the technological age or as some put it “the new oil,” “the next natural resources” and “currency of the 21th century” which everything depends on to function and operate. The Internet of Things (IoT) which aims to connect things to the Internet and interconnect them with each other could have a huge impact on data generation and dissemination as there will be data streams from countless sources. The centrality of data and its countless value in today’s world do not, however, end contention and controversial views about its nature. Every stakeholder looks at data from his own perspective. Merchants and the business community seem to deal with data as a valuable asset and commodity that could generate huge amount of profits. The importance of data and its financial value are not overlooked by the academic society but the way of dealing with it as property or something else remained unsettled. In their part, judges traditionally excluded information (data) from property ambit and current statutes seem to be silent. This paper attempts to study propertization of data in the light of contemporary business practice, academic discussion and some available court-cases in order to test the plausibility of these attitudes or in more accurate words to comprehend the wisdom lie behind these different stands. This paper is believed to be useful and timely as data propertization is an ongoing contentious issue that surfaces with every new wave of data-generated technology such as the IoT.